How does thermal scattering shape the infrared spectra of cloudy exoplanets? A theoretical framework and consequences for atmospheric retrievals in the JWST era. Issue 1 (1st July 2021) - Taylor, Jake; Parmentier, Vivien; Line, Michael R; Lee, Elspeth K H; Irwin, Patrick G J; Aigrain, Suzanne
ABSTRACT: Observational studies of exoplanets are suggestive of a ubiquitous presence of clouds. The current modelling techniques used in emission to account for the clouds tend to require prior knowledge of the cloud condensing species and often do not consider the scattering effects of the cloud. We explore the effects that thermal scattering has on the emission spectra by modelling a suite of hot Jupiter atmospheres with varying cloud single-scattering albedos (SSAs) and temperature profiles. We examine cases ranging from simple isothermal conditions to more complex structures and physically driven cloud modelling. We show that scattering from nightside clouds would lead to brightness temperatures that are cooler than the real atmospheric temperature if scattering is unaccounted for. We show that scattering can produce spectral signatures in the emission spectrum even for isothermal atmospheres. We identify the retrieval degeneracies and biases that arise in the context of simulated JWST spectra when the scattering from the clouds dominates the spectral shape. Finally, we propose a novel method of fitting the SSA spectrum of the cloud in emission retrievals, using a technique that does not require any prior knowledge of the cloud chemical or physical properties.